2017
DOI: 10.3389/fphar.2016.00513
|View full text |Cite
|
Sign up to set email alerts
|

Agrimonolide and Desmethylagrimonolide Induced HO-1 Expression in HepG2 Cells through Nrf2-Transduction and p38 Inactivation

Abstract: Agrimonolide and desmethylagrimonolide are the main bioactive polyphenols in agrimony with well-documented antioxidant, anti-diabetic, and anti-inflammatory potential. We report here for the first time that agrimonolide and desmethylagrimonolide stimulate the expression of phase II detoxifying enzymes through the Nrf2-dependent signaling pathway. Agrimonolide and desmethylagrimonolide also possess considerable protective activity from oxidative DNA damage. In order to explore the cytoprotective potential of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…The available researches confirm that MAPKs are not only one of the important signal pathways of mediating inflammatory reaction, but also involve in the regulation of Nrf2 transcription activity by inducing Nrf2 phosphorylation, although the above-mentioned regulation is only indirect. In different cells, after receiving various stimulation of external or chemical foreign matters, the results of MAPKs regulating Nrf2 may be different [20] , [21] , [22] . Our study showed that IL-1Ra could effectively inhibit MAPKs signal pathway activated by I/R damage, while further activating Nrf2/HO-1 signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The available researches confirm that MAPKs are not only one of the important signal pathways of mediating inflammatory reaction, but also involve in the regulation of Nrf2 transcription activity by inducing Nrf2 phosphorylation, although the above-mentioned regulation is only indirect. In different cells, after receiving various stimulation of external or chemical foreign matters, the results of MAPKs regulating Nrf2 may be different [20] , [21] , [22] . Our study showed that IL-1Ra could effectively inhibit MAPKs signal pathway activated by I/R damage, while further activating Nrf2/HO-1 signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin was also found to significantly reduce posttranslational levels of Keap1 protein [83]. However, the main bioactive polyphenols, agrimonolide (AM) and desmethylagrimonolide (DM), have been proved to facilitate Keap1 degradation to further accelerate the release of Nrf2 [88].…”
Section: Antioxidant Effects Of Polyphenols On Metsmentioning
confidence: 99%
“…SOD can transform superoxide into H 2 O 2 , and then, H 2 O 2 is catalyzed by CAT and GSH-Px. The Nrf2-ARE pathway was found to activate the endogenous protective system, facilitating antioxidant capacity in cells [88]. Song et al found that anthocyanin supplement upregulated the expressions of SOD and GSH-Px, and subsequently, attenuated lipid peroxidation in the serum, kidney, and liver in an aging mouse model [62].…”
Section: Antioxidant Effects Of Polyphenols On Metsmentioning
confidence: 99%
“…Anthocyanins are hydrophilic and water-soluble polyphenolic plant pigments and metabolites, which are one of the important antioxidants. They possess a wide range of pharmacological properties, such as antioxidant, antiaging, anti-inflammatory, antimicrobial and anti-cancer [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The following are available online at http://www.mdpi.com/2073-4360/11/12/2077/ s1,Figure S1: the images of optimized synthesis conditions of Fe3 O 4 /anthocyanin magnetic biocomposite. (a) anthocyanin and Fe 3 O 4 with different mass ratios of 5:1, 1:1, 1:5, 1:10, 1:20, 1:40, 1:80; (b) the optimum synthesis conditions of Fe 3 O 4 /anthocyanin magnetic biocomposite; (c) anthocyanin and Fe 3 O 4 with different mass ratios of 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70; (d) different reaction times of 2, 4, 6, 8, 10, 12, 14, 16, 18, 22 h; (e) different pH of3, 5, 7, 9, 11, 13; (f) different reaction temperatures of 20, 30, 40, 50, 60 • C, Figure S2: the images of release conditions of anthocyanin.…”
mentioning
confidence: 99%